Gambaran Hasil Peningkatan Kadar Hemoglobin Pada Pasien Anemia Yang Ditransfusi Dengan Packed Red Cell Dan Whole Blood Di Rsud Kabupaten Polewali Mandar - Ditaellyana Artha; I Kadek Artika Dwipayana (Jurnal Media Laboran, 2020)
Anemia occurs due to one or more combinations of three basic mechanisms, namely blood loss, decreased erythrocyte production, or increased erythrocyte destruction (hemolysis). Transfusion is a process of transferring blood or blood components from one person (donor) to another person (recipient). The purpose of this study was to determine the increase in hemoglobin levels in anemic patients after being transfused with Packed Red Cell and Whole Blood at Polewali Mandar Hospital. The research method is descriptive laboratory observation in which 10 samples of the research are taken from blood to be checked for hemoglobin levels. The results showed that the hemoglobin levels of anemic patients before and after being transfused with Packed Red Cell and Whole Blood. Based on the results of the study, it can be concluded that the average increase in hemoglobin (Hb) of posttransfusion anemia patients with Packed Red Cells is 0.98 g/dl, while the average increase in Hb levels after Whole Blood transfusion is 0.54 g/dl. Researchers suggest to laboratory workers to pay more attention to the increase in hemoglobin levels after transfusion before releasing the results, to further researchers to develop research by calculating the difference in the average increase in hemoglobin levels after Packed Red Cell and Whole Blood transfusions at the age of more than 40 years, and to people to read more books or articles about health in order to add more insight, especially in the health sector